Comparison between types of dressing following catheter insertion and early exit-site infection in peritoneal dialysis - Figueiredo, Ana Elizabeth; de Mattos, Carolina; Saraiva, Cristine; Olandoski, Marcia; Barretti, Pasqual [UNESP]; Pecoits Filho, Roberto; de Moraes, Thyago Proença (Wiley, 2017)
Aims and objectives: To investigate whether the type of dressing used (occlusive vs. semi-occlusive) impacts on exit-site infection. Background: The exit-site infections are a major predisposing factor for peritoneal dialysis-related peritonitis, the main cause of technique failure and an important cause of mortality. The care taken in exit-site dressing is considered an important procedure for the prevention of trauma and contamination of this area. Nevertheless, to our knowledge, no study has yet analysed the impact of different dressing types on early exit-site infection (up to two months after catheter insertion). Design: A prospective observational study involving the BRAZPD II (Brazilian Peritoneal Dialysis Multicenter Study) cohort. Methods: All incident patients with data available for dressing type applied following peritoneal dialysis catheter insertion were included in the study. A multilevel logistic regression model was used to compare the log-odds of exit-site infections between groups. Results: A total of 2460 incident patients were included. Occlusive and semi-occlusive dressings were applied in 82·6% (n = 2031) and 17·4% (n = 427) of patients, respectively. Exit-site infection incidence was not affected by the type of dressing used, with a logit for occlusive dressing of 2·15 (95% CI 0·81–5·70). The combined outcome of exit-site infection and tunnel infection also showed no significance between the groups (logit 1·46, 95% CI 0·72–2·97). Conclusion: Our results indicate that the type of exit-site dressing used during the healing phase following peritoneal dialysis catheter insertion has no impact on early exit-site infection rates. Relevance to clinical practice: Provides evidence to support the similarity between occlusive and semi-occlusive dressing regarding infection rates in exit site of peritoneal dialysis catheter, therefore allowing the choice to be made accordingly to routine or availability.
Keywords: chronic kidney disease; dressing; nursing; peritoneal dialysis